Proposal of a new specific cardiopulmonary exercise test for taekwondo athletes - Araujo, M. P.; Nóbrega, A. C. L.; Espinosa, G.; Hausen, M. R.; Castro, R. R. T.; Soares, P. P.; Gurgel, J. L. (The Journal of Strength and Conditioning Research, 2017)
The objective of this study is to evaluate the cardiorespiratory variables of Taekwondo athletes while performing incremental exercise test on an ergometer using a ramp protocol and to propose a specific protocol for assessing these physiological variables during Taekwondo practice. Fourteen athletes participated in 2 incremental exercise tests: a treadmill exercise test (TREADtest) and a Taekwondo-specific exercise test (TKDtest). The TKDtest consists in 1-minute stages of kicks with an incremental load between then. The subjects perform kicks each time a sound signal was heard. Heart rate (HR), oxygen uptake (VO2), and their reserve correspondents (VO2R and reserve heart rate [HRR]) were divided into quartiles to verify their kinetics along the tests. Significant difference between 2 tests was found only for VO2R (p = 0.03). Regarding the quartiles, significant differences were found for HR in the first (p = 0.030) and second (p = 0.003). Analyzing the regression curves, significant differences were found for HR for intercept (p = 0.01) and slope (p = 0.05) and HRR for slope (p = 0.02). Analysis showed that significant reliability, with intraclass correlation coefficient (ICC), was found for the VO2peak (ICC = 0.855, p = 0.003), VO2 in ventilatory thresholds 1 (ICC = 0.709, p = 0.03) and 2 (ICC = 0.848, p = 0.003). Bland-Altman analyses reported a mean difference ± the 95% limits of agreement of 2.2 ± 8.4 ml/kg/min to VO2peak. The TKDtest is reliable for measurement of cardiorespiratory variables, and the behavior of these variables differs mainly from TREADtest, probably because of the motor task performed.